Problematika Bank Islam di Daerah Minoritas Muslim - Kawin Malung; Makhrus Makhrus (UM Purwokerto Press, 2022)
This article examines the problems of Islamic banking in Muslim minority areas, especially Thailand. This type of research is a descriptive qualitative research object with the Islamic Bank Prachuap Khiri Khan Thailand, while the data collection techniques are interviews, observation, and documentation. Data analysis is carried out through synchronization between research data and theories that will support the conclusions of this study. The results of this study indicate that the Prachuap Khiri Khan branch of the Islamic bank faces several problems in carrying out its banking operations. These problems include, among others, factors in the banking world in Thailand, internal factors related to the banking system and also the employees who work at the Islamic Bank, as well as factors from the customers themselves, which in fact, the Thai Muslim community lacks enthusiasm for Islamic banks. The evaluation that has been carried out by Islamic Banks on the problems faced is to provide short courses to Islamic Bank employees, especially to employees at the front office because in that section they meet and socialize more directly with customers. Then, provide more intensive socialization through various social media, outreach to Islamic foundations or schools in Thailand to attract interest and cooperation between the two parties, and Islamic Banks from the center to branches conduct annual evaluations to improve the banking system. and improving the quality of banking services to customers of the Prachuap Khiri Khan Islamic Bank Branch.